Both Basal and Acute Restraint Stress-Induced c-Fos Expression Is Influenced by Age in the Extended Amygdala and Brainstem Stress Centers in Male Rats - Kovács, László Ákos; Schiessl, Josef Andreas; Nafz, Anna Elisabeth; Csernus, Valér; Gaszner, Balázs (Frontiers in Aging Neuroscience, 2018)
The hypothalamus-pituitary-adrenal axis (HPA) is the main regulator of the stress response. The key of the HPA is the parvocellular paraventricular nucleus of the hypothalamus (pPVN) controlled by higher-order limbic stress centers. The reactivity of the HPA axis is considered to be a function of age, but to date, little is known about the background of this age-dependency. Sporadic literature data suggest that the stress sensitivity as assessed by semi-quantitation of the neuronal activity marker c-Fos may also be influenced by age. Here, we aimed at investigating the HPA activity and c-Fos immunoreactivity 2 h after the beginning of a single 60 min acute restraint stress in eight age groups of male Wistar rats. We hypothesized that the function of the HPA axis (i.e., pPVN c-Fos and blood corticosterone (CORT) level), the neuronal activity of nine stress-related limbic areas (i.e., magnocellular PVN (mPVN), medial (MeA), central (CeA), basolateral nuclei of the amygdala, the oval (ovBNST), dorsolateral (dlBNST), dorsomedial (dmBNST), ventral and fusiform (fuBNST) divisions of the bed nucleus of the stria terminalis (BNST)), and two brainstem stress centers such as the centrally projecting Edinger-Westphal nucleus (cpEW) and dorsal raphe nucleus (DR) show age dependency in their c-Fos response. The somatosensory barrel cortex area (S1) was evaluated to test whether the age dependency is specific for stress-centers. Our results indicate that the stress-induced rise in blood CORT titer was lower in young age reflecting relatively low HPA activity. All 12 stress-related brain areas showed c-Fos response that peaked at 2 months of age. The magnitude of c-Fos immunoreactivity correlated negatively with age in seven regions (MeA, CeA, ovBNST, dlBNST, dmBNST, fuBNST and pPVN). Unexpectedly, the CeA, ovBNST and cpEW showed a considerable basal c-Fos expression in 1-month-old rats which decreased with age. The S1 showed a U-shaped age-related dynamics in contrast to the decline observed in stress centers. We conclude that the age- and brain area dependent dynamics in stress-induced neuronal activity pattern may contribute to the age dependance of the stress reactivity. Further studies are in progress to determine the neurochemical identity of neurons showing age-dependent basal and/or stress-induced c-Fos expression.